Influence Factors on Mechanisms of Superlubricity in DLC Films: A Review - Yu, Qingyuan; Chen, Xinchun; Zhang, Chenhui; Luo, Jianbin (Frontiers in Mechanical Engineering, 2020)
As a kind of self-lubricating material, diamond-like carbon (DLC) film is famous for its excellent tribological properties. Superlubricity state with nearly-vanishing friction achieved with DLC film has enormous potential applications in future mechanical systems. It is pointed out that its superlubricity state is highly related to both the inherent properties of the DLC film and external sliding conditions. Moreover, the underlying mechanisms of the superlubricity are complicated, posing uncertainties on their engineering application. This review provides an overview of the influence factors, including film composition, ambient, temperature, normal load and sliding velocity and their correlations with the anti-friction behaviors of DLC films. These understandings will enable a more effective engineering application of self-lubricating carbon films with excellent tribological properties.